The first reported case of Beaulieu-Boycott-Innes syndrome caused by two novel mutations in THOC6 gene in a Chinese infant. Issue 15 (April 2020) - Zhang, Qiang; Chen, Shaoke; Qin, Zailong; Zheng, Haiyang; Fan, Xin
Abstract: Rationale: This case report expands the mutation and phenotypic spectra of Beaulieu-Boycott-Innes syndrome (BBIS), and will be valuable for mutation-based pre- and post-natal screening of BBIS when conducting a genetic diagnosis. Patient concerns: A 4-year old boy from Guilin City, Guangxi Zhuang Autonomous Region, China, was referred to our clinic for clarification of his diagnosis because he showed moderate intellectual disability. Diagnosis: Two novel compound heterozygous mutations of THOC6, c.664T>C (p.Trp222Arg) and c.945+1 G>A were identified in this patient by whole exome sequencing. The two mutations were evaluated as pathogenic and likely pathogenic respectively according to the American College of Medical Genetics guidelines. This is the first case displaying the BBIS phenotype reported in the Chinese population. These two mutations have not been reported previously. Interventions: Symptomatic treatment and rehabilitation training for patients. Outcomes: The genetic cause of the disease was identified. The family received scientific genetic counseling. Lessons: BBIS is a rare syndromic autosomal recessive disease with intellectual disability and it is normally difficult for clinicians to recognize it. Whole exome sequencing is an efficient way to identify the gene which causes a particular disease in patients.